Green Waqf: A Pathway to Achieving Climate Action and Sustainable Development Goals (SDGs) - Rozi Andrini; Razali Razali; Muhammad Deni Putra; Haniah Lubis; Iskandar Ibrahim (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study maps the intellectual landscape of Green Waqf research and identifies its dominant themes and future directions for climate action and sustainable development. Employing a thematic literature review across major academic databases, the research synthesizes scholarly publications to examine the evolution and governance challenges of Green Waqf scholarship. The findings reveal four thematic clusters waqf asset management, Islamic finance instruments, environmental sustainability, and institutional governance. Green Waqf scholarship has evolved from fragmented conceptual discussions toward more empirically grounded research, yet significant gaps persist in empirical validation and governance frameworks. The study argues that Green Waqf represents a promising yet institutionally contested pathway for integrating Islamic philanthropy into climate action, constrained by regulatory fragmentation, limited professional capacity, transparency deficits, and inadequate policy integration. The findings offer policy-relevant insights for strengthening Islamic philanthropy’s role in climate action and sustainable development.